National codes of media culture on the example of precedent texts of kazakhstani and russian media (Herald of Journalism, 2022)
The article is devoted to the problem of definition and interpretation of national codes of media culture. The relevance of the study is due to the ambiguity of the reaction of national socio-cultural communities to the information activities of the media. A new kind of cultural experience, obtained through the media, forms a convergent public consciousness, which has its own culture translation code - the media code.The purpose of the study is to reveal the peculiarity of media culture codes, which is revealed through the concept of insight, corresponding to the technical nature of media communication. To analyze the discourse of Kazakhstani and Russian researchers on the issue of precedent media texts.The research methodology is based on the ideas of the cultural code of the classics of cultural semiotics - Yu.M. Lotman, C. Rapaille, W. Eco, N. Luhmann, R. Barthes and the theory of hermeneutics of G. Gadamer. It is shown that the lack of awareness of cultural preferences, the cultural code, the contexts of values ​​and norms leads to a lack of critical perception of the verbal and visual messages of media culture.The scientific ideas of the research - knowledge of reality, where during the second half of the twentieth century the theory of correlation of signs and images with culture, society and human life experience is being formed, allows us to talk about dynamic and static codes of culture, which are embodied in the media environment. It is determined that in the media discourse there is always an incorporation of world experience into the national culture, the understanding of media texts is carried out only with the limitation of preliminary opinions, therefore, the selection of static and dynamic codes of modern national culture will help to stabilize both the mechanisms of communication and the transmutation of culture.Keywords: media culture code, code interpretation, media text understanding, national cultural code, media culture.